Laterality of Attentional Networks in Patients With Cerebral Small Vessel Disease - Cao, Shanshan; Zhang, Jun; Wang, Zhiqi; Pan, Wen; Tian, Yanghua; Hu, Panpan; Wei, Qiang; Wang, Jingye; Shi, Xiuli; Wang, Kai (Frontiers in Aging Neuroscience, 2020)
Introduction: Problems with attention are common in patients with cerebral small vessel disease (CSVD). The normal human brain exhibits functional and structural asymmetry. However, it is unknown whether there is lateralization of attention in patients with CSVD. Objective: This study aims to investigate attention separately in both cerebral hemispheres in patients with CSVD using the computer-based Lateralized Attention Network Test—Revised (LANT-R). Methods: The total number of subjects included was 58, which includes the CSVD (N = 35) and healthy control (HC, N = 23) groups. All subjects completed the LANT-R paradigm and neuropsychological background tests. Results: The results indicate that there is an left hemisphere (LH) lateralization in orienting network efficiency in the HC group. However, this lateralization was not apparent in the CSVD group. Furthermore, the difference between groups was significant (interaction P = 0.02). In addition, the scores of subjects in the CSVD group are lower in several cognitive domains, including attention function, memory function, information processing speed, and executive function, compared with the controls. Conclusion: Patients with CSVD change in the lateralization of attention compared with the normal elderly. The decrease in attention in patients with CSVD might be caused by the reduced ability of selecting useful information in the LH.